Impact of a Web-Based Nutrition Intervention on Eating Behaviors and Body Size Preoccupations among Adolescents - Manon Bordeleau; Maya Purcell; Véronique Provencher; Shirin Panahi; Raphaëlle Jacob; Natalie Alméras; Vicky Drapeau (MDPI AG, 2023)
We aimed to evaluate the impact of a web-based school nutrition intervention on eating behavior traits, body weight concern, body size perception and body size dissatisfaction in adolescents. Ten classes of secondary students in Canada (13.6 ± 0.8 years) were randomized into an intervention (n = 162 students) or control group (n = 75 students). Adolescents in the intervention, conducted between 2011 and 2013, participated in an online nutrition challenge to increase their consumption of vegetables, fruits and dairy products using a web-based platform over six weeks. Measurements were taken at baseline (PRE) and post-intervention (POST). No significant negative changes were observed between the intervention and control groups for eating behavior traits, body weight concern, body size perception and dissatisfaction. However, results suggest a trend for a positive effect of the intervention on susceptibility to hunger in boys (group × time interaction, p = 0.10). Specifically, boys experienced a reduction in their susceptibility to hunger in response to the intervention (PRE: 6.1 ± 3.8, POST: 4.8 ± 3.7, p = 0.009). An intervention aimed at improving the eating habits of adolescents did not negatively influence body size preoccupations. In response to the intervention, boys tended to show a lower susceptibility to hunger, which might help them to prevent overeating and adopt healthy eating habits.